EPEN-06. YAP1 SUBGROUP SUPRATENTORIAL EPENDYMOMA REQUIRES TEAD AND NUCLEAR FACTOR I-MEDIATED TRANSCRIPTIONAL PROGRAMS FOR TUMORIGENESIS. (23rd April 2019) - Pajtler, Kristian; Wei, Yiju; Okonechniov, Konstantin; Vouri, Mikaella; Sahm, Felix; Bunt, Jens; Jones, David; Korshunov, Andrey; Lichter, Peter; Pfister, Stefan; Kool, Marcel; Li, Wei; et al.
Abstract: Ependymoma (EPN) is one of the most aggressive pediatric brain tumors, often arising in the supratentorial (ST) region. Our previous DNA methylation profiling study has identified ST-EPN subgroups that are characterized by YAP1-related fusions through genomic structural rearrangements (hereafter called as ST-EPN-YAP1). No reports of amplification and hyper-activation of the YAP1 gene in ST-EPN-YAP1s postulate that YAP1-related fusions could have unique oncogenic function(s) in this type of cancer. Nevertheless, the lack of adequate models for ST-EPN-YAP1 had hindered the discovery of YAP1-fusion-specific molecular mechanisms in EPN tumorigenesis and the development of effective targeted therapies for these tumors. Most recently, we developed a murine ST-EPN-YAP1 model by forced expression of YAP1-MAMLD1, the most dominant type of the fusion proteins in ST-EPN-YAP1 into cortical progenitors using in utero electroporation. Detailed histological analysis suggest that tumors arose from Pax6-positive neural stem cells, which is highly consistent with the highest expression of PAX6 in human ST-EPN-YAP1s across all EPN subgroups. MAMLD1-driven nuclear localization of the fusion protein is strongly associated with tumorigenesis. To investigate oncogenic functions of YAP1-MAMLD1, we performed a ChIP-seq analysis on human ST-EPN-YAP1 primary tumors with an anti-YAP1 antibody. Intriguingly, ST-EPN-YAP1-specific enhancers enriched for YAP1 peaks exhibited abundant transcriptional factor binding motifs of nuclear factor I and TEADs. Co-immunoprecipitation revealed that both TEAD and NFIA/B interact with YAP1-MAMLD1. Both the mutation of the TEAD binding site in the YAP1 fusion and dominant-negative inhibition of NFI proteins prevented tumor induction in mice. Collectively, we demonstrated that YAP1-MAMLD1 function as an oncogenic driver in ST-EPN-YAP1s through recruitment of TEAD and NFI transcriptional factors.